2014
DOI: 10.1371/journal.pone.0112377
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variants of C. elegans Demonstrate Defects in Both Sperm Function and Oogenesis at Elevated Temperatures

Abstract: The temperature sensitivity of the germ line is conserved from nematodes to mammals. Previous studies in C. briggsae and Drosophila showed that isolates originating from temperate latitudes lose fertility at a lower temperature than strains originating from tropical latitudes. In order to investigate these relationships in C. elegans, analysis of the fertility of 22 different wild-type isolates of C. elegans isolated from equatorial, tropical and temperate regions was undertaken. It was found that there are si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
80
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(96 citation statements)
references
References 33 publications
(50 reference statements)
15
80
1
Order By: Relevance
“…As expected from prior studies (e.g. Gems et al ., 1998; Petrella, 2014), brood size was markedly lower for all worms at 25 than 15 °C (Fig. 5D).…”
Section: Resultsmentioning
confidence: 91%
“…As expected from prior studies (e.g. Gems et al ., 1998; Petrella, 2014), brood size was markedly lower for all worms at 25 than 15 °C (Fig. 5D).…”
Section: Resultsmentioning
confidence: 91%
“…However, although adult worms can withstand short periods of heat shock (Lithgow et al, 1995), it affects their fertility (Aprison and Ruvinsky, 2014). Growth temperatures above 25 C are stressful for C. elegans and lead to sterility; this is true for natural isolates as well as the lab strain N2 (Matsuba et al, 2013;Hirsh et al, 1976;Anderson et al, 2011;Petrella, 2014). To date, five distinct clades of C. briggsae natural isolates have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Byerly et al 1976;McMullen et al 2012;Petrella 2014, but see Zhang et al 2015). The decrease of reproductive function at high temperatures seems to be associated with functioning of both spermathogenic and oogenic germ lines (Aprison and Ruvinsky 2014;Petrella 2014), although the relative contribution of these two factors varies between strains (Petrella 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the pattern observed in our study could have resulted from male and/or female gamete production failure. Indeed, it has been shown that increased temperature affects sperm and oocyte production, ovulation and spermatid activation in C. elegans (Aprison and Ruvinsky 2014;Petrella 2014). We might also expect thermal stress to result in elevated gamete death (McMullen et al 2012) as increased temperature during ovulation has been shown to reduce gamete viability in some fish species (Pankhurst and Van Der Kraak 1997).…”
Section: Discussionmentioning
confidence: 99%